Dancing Diplomacy in the Digital Era: A Qualitative Content Analysis of @ktti.kbriseoul’s Cultural Narratives - Muhammad Wildan Khunaefi; Monika Sri Yuliarti; Hartati Sulistyo Rini (Universitas Negeri Semarang, 2026)
Prevailing state-centered frameworks in cultural diplomacy have largely neglected the dynamic representational practices of diaspora communities in digital spaces. Scholarly inquiry into how diasporas construct cultural and gendered identities via social media remains scarce, particularly within dance, a medium embodying the dialectics of gender, diplomacy, and national identity. This study analyses the Instagram account @ktti.kbriseoul, curated by the Indonesian Traditional Dance Group in Seoul, to examine its role in enacting gender negotiation, cultural diplomacy, and community representation. Through thematic content analysis of visual and narrative posts between June and July 2024, the research reveals patterns of visual composition, embodied performance, and networked relations that transcend mere documentation. The account functions as an active site of meaning-making, shaped by algorithmic logics and cross-cultural expectations, where narratives manifest as sustained performative practices of gender, hybrid identity, and diasporic emotional exchange. The findings advance theoretical discourse by shifting cultural diplomacy from institutional to participatory terrains, situating diaspora members as cultural agents who mediate identity through technology, performance, and visual engagement. This study underscores the diaspora’s agency in producing cultural narratives that navigate and reshape both global configurations and the architectures of digital media.